Entrepreneurial Orientation of Garlic Producers (Indian Journal of Extension Education, 2011)
The study was conducted in Neemuch district of Madhya Pradesh to investigate the entrepreneurial orientation of garlic producers in terms of socio – personal, agro-economic, extension communication and socio-psychological traits. The data collected from 120 randomly selected respondents revealed that 66.67 per cent of garlic growers were having medium level of entrepreneurial orientation. The study also revealed that the variables viz. age, educational status, social participation, information source utilization, mass media exposure, cosmopoliteness and economic motivation had significant influence on entrepreneurial orientation of garlic producers.